Strong Foundation Of Freedom, Justice And Equality In Our Country (On The Example Of The Constitution Of The Republic Of Uzbekistan) - Kariyeva Halima Ikromjonovna (Genius Journals, 2021)
This article interprets the concept of human, as well as concepts such as social security, freedom, justice, equality, on the example of the articles of the Constitution of the Republic of Uzbekistan
Keywords: Constitution of the Republic of Uzbekistan; citizen; individual; person